2013
DOI: 10.1002/ptr.5082
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Melanin Synthesis by Rengyolone Isolated from the Root of Eurya emarginata in Melan‐a Cells

Abstract: In the course of screening for the melanogenesis inhibitors, rengyolone was isolated from Eurya emarginata (Thumb) Makino. Its chemical structure was determined on the basis of spectroscopic analysis including mass spectroscopy and nuclear magnetic resonance analysis. Rengyolone inhibited potent melanogenesis in melan-a cells with an IC50 value of 65 μM without cytotoxicity. Also, rengyolone showed a melanin biosynthesis inhibition zone in a culture plate of Streptomyces bikiniensis, which is commonly used as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Intriguingly, the two fractions with different chemical composition, exerted complementary and nonoverlapping activities on different skin cells, as proved by cellular and molecular assays. In particular, the tyrosinase inhibiting properties of the root extracts or root‐isolated compounds have recently attracted attention . We found that BrWEt, containing phenylpropanoids and glucosidic derivatives, was able to significantly inhibit intracellular tyrosinase activity and melanin content in melanocytes.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Intriguingly, the two fractions with different chemical composition, exerted complementary and nonoverlapping activities on different skin cells, as proved by cellular and molecular assays. In particular, the tyrosinase inhibiting properties of the root extracts or root‐isolated compounds have recently attracted attention . We found that BrWEt, containing phenylpropanoids and glucosidic derivatives, was able to significantly inhibit intracellular tyrosinase activity and melanin content in melanocytes.…”
Section: Discussionmentioning
confidence: 98%
“…Root‐secreted compounds, such as glucosinolates, terpenoids, organic acids and flavonoids, as well as cell‐wall‐linked glycoproteins, represent a reservoir of defensive compounds which the plants use to protect themselves against pathogenic attacks and/or to enhance the natural defense response mechanisms . One of the most used defense mechanisms, that the roots employ, is the inhibition of tyrosinase activity, because melanin is one of the most widely distributed pigments found in bacteria, fungi, and animals …”
Section: Introductionmentioning
confidence: 99%
“…Angiogenic/anti-angiogenic Lam et al, 2008;He et al, 2009a;He et al, 2009b;Hong et al, 2009;He et al, 2010;Alex et al, 2010;KRILL et al, 2010;Zhu et al, 2011;Liu et al, 2011;Crawford et al, 2011;Tse et al, 2012;Zhong et al, 2012;He et al, 2012;Zhang et al, 2012;Han et al, 2012;Yu et al, 2013;Ba et al, 2013;Lee et al, 2013;Yahg et al, 2013;Fan et al, 2013;Yue et al, 2013, Da-Song et al, 2014Zhou et al, 2014;Germano et al, 2014Lai et al, 2015Antithrombotic activity Song et al, 2012Shi et al, 2015anticonvulsant Orellana-Paucar et al, 2012Buenafe et al, 2013;Challal et al, 2014Anti-inflammatory Kao et al, 2010Bohni et al, 2013;Wang et al, 2013Antilipemic Jin et al, 2011Kim et al, 2012;Pardal et al, 2014;Littleton et al, 2014Melanogenic Kim et al, 2008Ding et al, 2011;Park et al, 2013;Kim et al, 2014;Wang et al, 2014Neurodegenerative diseases Zhang 2012Chong et al, 2013;…”
Section: Activity Assayed In Zebrafish Model Referencesmentioning
confidence: 99%